Efficacy of epidural injection of steroid in treatment of lumber disc prolapse: article review - Musaed hekmat AL-Dahhan (Al Muthanna University, 2021)
Chronic low back and lower extremity pain is mainly caused by lumbar disc herniation (LDH) and radiculitis. Various surgery and nonsurgical modalities, including epidural injections, have been used to treat LDH or radiculitis. Caudal epidural injection of local anesthetics with or without steroids is one of the most commonly used interventions in managing chronic low back and lower extremity pain. To describe the indications, rationale, techniques, alternatives, contraindications, complications, and efficacy of lumbar and caudal epidural corticosteroid injections. Interventions: Three reviewers with formal training and certification in evidence-based medicine searched the literature on non–image guided lumbar interlaminar epidural steroid injections. A larger team of seven reviewers independently assessed the methodology of studies found and appraised the quality of the evidence presented. A systematic literature search was performed, in the Medline Case reports and retrospective and prospective studies were extensively reviewed to provide detailed descriptions of the clinical features of lumbar and caudal epidural corticosteroid injections. Data sources included relevant literature of the English language identified through searches of PubMed and EMBASE , and manual searches of bibliographies of known primary and review articles. Epidural corticosteroid injections are commonly requested treatments for patients with various low-back or lower-extremity pain syndromes (or both). Most of the reports on the use of this type of treatment are retrospective and noncontrolled. These studies indicate benefit; however, the prospective controlled studies provide varied results about the efficacy of lumbar and caudal epidural corticosteroid injections. In conclusions: In patients with lumbar radicular pain secondary to disc herniation or neurogenic claudication due to spinal stenosis, interlaminar epidural steroid injections appear to have clinical effectiveness limited to short-term pain relief. Therefore, in a contemporary medical practice, these procedures should be restricted to the rare settings where fluoroscopy is not available.